Stabilizing Vehicle Lateral Dynamics with Considerations of State Delay of AFS for Electric Vehicles via Robust Gain‐Scheduling Control. Issue 1 (21st May 2015) - Jin, XianJian; Yin, Guodong; Li, Yanjun; Li, Jianqiu
Abstract: This paper presents a robust gain‐scheduled H ∞ controller to improve lateral stability and handling of four‐wheel‐independent‐drive electric vehicles possessing active front steering system with considerations of state delay. The time delay for the state is assumed as uncertain time‐invariant but has a known constant bound. By considering the tyre cornering stiffness represented by the norm‐bounded uncertainty and the time‐varying longitudinal velocity described by a polytope with finite vertices, and the vehicle lateral dynamics model is converted into the uncertain vehicle linear parameter‐varying (LPV) state‐delayed system. The resulting delay‐dependent robust gain‐scheduling state feedback H ∞ controller is finally designed utilizing the constructed Lyapunov‐Krakovskii functional, and solved via a set of delay‐dependent linear matrix inequalities (LMIs). Simulations for various driving scenarios are implemented using MATLAB/SIMULINK‐CARSIM. The simulation results show the effectiveness of the proposed controller.